How transformational leadership reduces teachers’ role stress: dual mediation of affective commitment and job satisfaction - Yong, Ping; Zhang, Junhui (Frontiers in Psychology, 2025)
IntroductionTeacher stress is a growing concern in educational settings worldwide. Grounded in the Conservation of Resources (COR) theory, this study investigates how principals’ transformational leadership influences role stress among primary and secondary school teachers. It particularly focuses on the mediating roles of affective commitment and job satisfaction.MethodsA quantitative survey was conducted among 433 teachers in China. Data were analyzed using structural equation modeling (SEM) and the PROCESS macro to explore both direct and indirect effects of transformational leadership on teacher role stress.ResultsTransformational leadership was found to significantly reduce teachers’ role stress (direct effect = −0.185, 95% CI = [−0.277, −0.093]). Additionally, both affective commitment and job satisfaction served as significant mediators. Affective commitment exerted the strongest individual mediating effect (standardized indirect effect = −0.045, 95% CI = [−0.072, −0.021]), while the sequential mediation pathway involving both variables also reached statistical significance (standardized indirect effect = −0.018, 95% CI = [−0.031, −0.008]).DiscussionThe study found that transformational leadership reduces teachers’ role stress both directly and indirectly through affective commitment and job satisfaction. These results extend the application of COR theory by identifying emotional and motivational factors as key mediators. The findings also offer practical implications for enhancing teacher well-being through school leadership development.